Public health financing in Brazil (2019–2022): an analysis of the national health fund and implications for health management - Nunes Marinho, Luiza; Campbell, Stephen M.; da S. T. Amaral, Isabela Barboza; Reis e Silva, Rebeca; Godman, Brian; Meyer, Johanna C.; Godói, Isabella Piassi D. (Frontiers in Public Health, 2025)
IntroductionThe Unified Health System (SUS) in Brazil provides free, universal health services to all inhabitants of the country. This study aims to describe the allocation of public health resources in Brazil, both overall and across regions, based on National Health Fund (FNS) data from 2019 to 2022. The goal is to provide an understanding of the profile and distribution of resources sourced exclusively from the federal government during this period.MethodsA quantitative, descriptive study using data extracted from the FNS portal covering the period 2019–2022, along with publications and open data linked to Brazil’s Ministry of Health, was undertaken. Data collection included the resources allocated to health within each of the financing blocks (operational and investment), according to FNS as well as the Transparency Portal of the Office of the Comptroller General for more information about the COVID-19 pandemic.ResultsA total of USD 75.310 billion (406.283 billion BRL) was allocated to health services between 2019 and 2022, with 64.6% allocated to Specialized, Medium, and High Complexity Care and 30.2% to Primary Health Care (USD 21.096 billion). A lower percentage was dedicated to investment actions within the SUS, and there was heterogeneous distribution of resources across the country’s regions, with the Southeast receiving the most resources (38.5%), while the Central-West region received only 7.7%. In addition, more than USD 111 billion (600 billion BRL) was allocated by the federal government to the COVID-19 pandemic response, not exclusively for health-related purposes.ConclusionThe distribution profile of resources transferred from the FNS reflected population sizes but it is less clear whether resources were allocated based on need. Overall, there was a scarcity of resources allocated to areas such as investment. However, the COVID-19 pandemic represented a considerable impact on government funds. Health and social needs must be assessed and considered going forward to improve the allocation of resources within a unified health system.